Case reportIs the “porcellain homograft” a contraindication for transcatheter pulmonary valve implantation? A case report - Demkow, Marcin; Rużyłło, Witold; Biernacka, Elżbieta K.; Różański, Jacek; Kuśmierczyk, Mariusz (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2011)
A male patient had a repeat surgical right ventricular outflow reconstruction with the aortic homograft, for pulmonary atresia at the age of 7 years. At the age of 17 a homograft dysfunction (with predominant stenosis) developed and he was admitted for transcatheter pulmonary valve implantation. Severe calcifications of the total homograft wall were recognized. A homograft rupture with contrast extravasation to the mediastinal space occurred at the superior margin of the stent implanted for valve presenting. A covered stent was implanted to cover the leak, but this resulted in a second homograft rupture at the distal margin of the stent. The extravasation was estimated to be small and stable, and a Melody pulmonary valve was successfully implanted on a 20 mm system. Repeat planned angiography 4 days after the procedure revealed significant enlargement of the pseudoaneurysm and the patient was sent for surgery. Right ventricular outflow was uneventfully reconstructed with a pulmonary homograft. Excised old aortic homograft walls had an eggshell appearance. We suggest that a “porcelain” aortic homograft should be a contraindication for transcatheter pulmonary valve implantation.